1. Award for best research study (Validation and cultural adaptation in Greek of the ”Bullying in Nursing Education Questionnaire (BNEQ)” in university nursing students. Kalafati M, Nieri A, Dede M, Kapritsiou M, Karanikola M, Tziaferi S Mpouzika M, Lemonidou M. 46th National Conference of the Hellenic Nurses Association, 8-11 May 2019, Milos island, Greece._CLONE - Karanikola, Maria (My University, 2026)
1. Award for best research study (Validation and cultural adaptation in Greek of the ”Bullying in Nursing Education Questionnaire (BNEQ)” in university nursing students. Kalafati M, Nieri A, Dede M, Kapritsiou M, Karanikola M, Tziaferi S Mpouzika M, Lemonidou M. 46th National Conference of the Hellenic Nurses Association, 8-11 May 2019, Milos island, Greece.
Keywords: Sciences